DURANTA REPENS LINN. (VERBENACEAE): A COMPREHENSIVE REVIEW OF PHARMACOGNOSTIC, ETHNOMEDICINAL, PHARMACOLOGICAL, AND PHYTOCHEMICAL ASPECTS - Puri, Abhijeet V (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This review is intended to investigate the published report regarding phytochemical, ethnomedicinal, and pharmacological activities and put forth the therapeutic potential of Duranta repens Linn. (D. repens). It belongs to the family Verbenaceae, one of the therapeutically important plants, broadly distributed all throughout the world. It is commonly referred as golden dewdrop, angel whisper, pigeon berry, or skyflower. Methods: I utilized logical writing and scientific literature regarding D. repens by referring search engine such as Springerlink, ScienceDirect, SciFinder, PubMed, Scopus, Google Scholar, and BioMed Central as well as relevant books, websites, scientific publications, and dissertations as a source of information that provided an up-to-date review. My work on morphology and extraction of various phytochemicals and their evaluation has helped to provide an insightful account of D. repens. Results: Phytochemical profiling of these species revealed the presence of some imperative phytochemicals such as alkaloids, flavonoids, glycosides, phenolics, saponins, steroids, tannins and terpenoids as the basis of its valuable therapeutic properties. The other imperative phytoconstituents which contribute to the therapeutic properties are durantol, repennoside, repenins, and scutellarein. The pharmacological activities exhibited by D. repens as antimicrobial, antioxidant, and insecticide properties are attributed to the presence of valuable bioactive phytoconstituents. Conclusion: Considering these facts, I endeavored to present a comprehensive review enlightening the phytochemistry and pharmacological activities of plant D. repens. Future research can be directed to an extensive investigation about phytochemistry, clinical trials, pharmacokinetics, and acquiring safety data so as to add new dimensions to the therapeutic utilization of D. repens and other Duranta species.